2015
DOI: 10.1021/ie504557a
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Optimization for Power De-Rate Reduction in the Integrated Coal-Fired Power Plant with Carbon Capture and Storage

Abstract: Carbon capture and storage (CCS) has attracted worldwide attention as a near-term technology to decelerate global warming. Postcombustion CO 2 capture utilizes existing coal-fired power plants, and aqueous monoethanolamine (MEA) scrubbing is the most common capture technology. However, the heat and energy requirements of solvent regeneration and CO 2 liquefaction cause a 30% decrease in net power output. This power de-rate is a major obstacle to implementing CCS. In this study, simulation-based parametric opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
(42 reference statements)
0
1
0
Order By: Relevance
“…Besides, for researching and developing advanced materials and devices for ultrahigh vapor parameter coal-fired power generation (700 °C projects) and optimizing the control strategies and technologies for plant operations, exploration of new power cycles with higher efficiency has also become an important technical way to break through the bottleneck of coal-fired generation processes. Recently, the supercritical carbon dioxide (S-CO 2 ) power cycle, which has been widely applied in nuclear energy, concentrated solar energy (CSP), ship propulsion system, and waste heat recovery, has been receiving increasing interest in the field of fossil-fired generation in consideration of its high efficiency, compact structure, stable physical properties, and qualitative flexibility. Studies indicated that the S-CO 2 coal-fired power cycle can offer about 6% lower heating value (LHV) and relative efficiency improvement performances theoretically compared with the steam cycle, which attracts great interest and potential to be applied in the coal-fired power generation industry.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, for researching and developing advanced materials and devices for ultrahigh vapor parameter coal-fired power generation (700 °C projects) and optimizing the control strategies and technologies for plant operations, exploration of new power cycles with higher efficiency has also become an important technical way to break through the bottleneck of coal-fired generation processes. Recently, the supercritical carbon dioxide (S-CO 2 ) power cycle, which has been widely applied in nuclear energy, concentrated solar energy (CSP), ship propulsion system, and waste heat recovery, has been receiving increasing interest in the field of fossil-fired generation in consideration of its high efficiency, compact structure, stable physical properties, and qualitative flexibility. Studies indicated that the S-CO 2 coal-fired power cycle can offer about 6% lower heating value (LHV) and relative efficiency improvement performances theoretically compared with the steam cycle, which attracts great interest and potential to be applied in the coal-fired power generation industry.…”
Section: Introductionmentioning
confidence: 99%